Novel antagonists reveal the mechanism of PXR inhibition - Kamaraj, Rajamanikkam; Pavek, Petr (Trends in pharmacological sciences, 2024)
The pregnane X receptor (PXR) is a key regulator of metabolism, but the mechanisms underlying its antagonism remain unclear. Garcia-Maldonado et al. reported potent new antagonists and their co-crystal structures, revealing molecular determinants of PXR antagonism and paving the way for developing antagonists as therapeutics and preventing undesirable PXR activation.
Keywords: crystal structures; Humans; zvířata; Pregnane X Receptor; PXR; antagonist; Animals; pregnanový X receptor; lidé; drug discovery